Red Antz book shop / Larry Paulus... [et al.] - Paulus, Larry; Wan Ahmad, Wan Norhaniza; Wan Mohamad, Wan Maliza; Mohd Yusof, Ruhaidah (Faculty of Hotel And Tourism Management, 2004)
The name of our group business is Red Antz Book Shop. The nature of our business is a partnership form. Mainly, our industry profile is selling magazines, newspaper as well as novels. Furthermore, our business also focuses on book rental to our customers. We started our business with the total capital amounting RM60, 000.00, with 5 staffs to operate it. This includes, General Manager, Administration Executive, Marketing Executive, Operation Executive, Financial Executive and cleaner. Red Antz Book Shop conveniently located in Grace Court, Sembulan. The date of commencement of our business is on I st January 2005. We have chosen to create this type of business due to the high demand of the residents of Grace Court and Taman Sempelang. This is because currently, there is only one shop that sells reading materials to the residents. Furthermore, this type of business is beneficial to both entrepreneur and the customers. The reason behind this because the time spent in the shop will also not be wasted by reading. Another factor that indeed contributing our choice of business is to develop new trend in the current location, that is to create a reading community. The future prospects of our business are to expand our business equipped with more highly trained staff, more choices on the reading materials and preferably developing our own book publishing company.